Direct‐acting antiviral drugs for the treatment of chronic hepatitis C virus infection: Interferon free is now. Issue 4 (31st August 2015) - Florian, J; Mishra, P; Arya, V; Harrington, P; Connelly, S; Reynolds, KS; Sinha, V
Abstract : Chronic hepatitis C (CHC) is a global, serious, and life‐threatening disease. Virologic response at 12 weeks post‐treatment (SVR12) signifies a durable virologic response and is currently the primary efficacy endpoint used in registrational trials. This change led to more rapid clinical development and earlier approvals of highly effective and well‐tolerated therapies, facilitating access to those in need. Hepatitis C virus (HCV) infection is a therapeutic area where mathematical modeling has proven helpful in understanding the drug mechanism and characterizing viral kinetics to inform therapy decisions. The availability of direct‐acting antivirals (DAAs) provides various treatment options for HIV/HCV coinfected patients, but the complexity of predicting and managing drug–drug interactions presents a unique challenge. Real‐world experience or noninterventional studies can provide insight regarding the safety and use of therapeutics that may not be readily available from traditional clinical trials. This article provides a brief overview of the development of promising drugs for the treatment of CHC.